Skin Electronics from Biocompatible In Situ Welding Enabled By Intrinsically Sticky Conductors - Lixue Tang; Shuaijian Yang; Kuan Zhang; Xingyu Jiang (Advanced Science, 2022)
Abstract Welding usually involves high temperatures, toxic solvents, or conditions not compatible with human bodies, which severely limit the fusion of electronics and human tissues. To achieve direct welding of electronics on human skin, the intrinsically sticky conductors that can simultaneously achieve metal‐grade electrical conductivity (≈41 7000 S m−1), hydrogel‐grade stretchability (>900% strain), and self‐adhesiveness (1.8 N cm−1) are reported. The sticky conductors composed of gallium indium alloy and acrylate polymer adhesives have a surface‐enriched structure, which can form instant mechanical and electrical connections with different surfaces through gentle pressure without involving conditions that may damage human tissues. Based on the sticky conductors, the in situ welding of electronics on the skin is realized. To demonstrate the feasibility of in situ welding, electronic tattoos are achieved for movement monitoring. Intrinsically sticky electrodes that can resist drying and simultaneously deform with the skin for electrophysiological measurement are also developed.